A history of international law in Italy - Bartolini, Giulio (Oxford : Oxford University Press, 2020)
This volume provides a comprehensive, innovative, and critical analysis of the development and impact of international law in Italy. Through its scholars and due to political and historical events, Italy has contributed significantly to the formation and definition of international law and its academic community.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 23, 2020).
Keywords: International law -- Italy; Law; International law